Rela????o do ??ngulo de cifose dorsal com o deslocamento do centro de press??o em idosas - Lopes, Bruno Sousa (2016)
The objective was to evaluate the influence of the angle of thoracic kyphosis in pressure center displacement in elderly while conducting a functional activity. The aged of Centro de Conviv??ncia do Idoso were selected for carrying out measurement of thoracic kyphosis angle from Flexicurve method. The postures of 153 elderly women were evaluated, using at least 25 with kyphosis and 25 with normal standard curve for the study follow-up. Following, physical therapy evaluation was performed to identify the elderly ineligible for the study, then the balance tests were conducted static and with functional reach test (FRT) associate with baropodometry platform. Also, elasticity tests were performed with Well???s bank. The Mann-Whitney test was used to establish the comparison of variables: age; anthropometric data; FRT; Well???s bank; and data obtained by the F-Scan. Also Pearson correlation was performed to correlate the degree of thoracic kyphosis with the results of FRT; and to establish the correlation between the thoracic kyphosis and the data obtained with the F-Scan. And also for correlate the result of the FRT with Fscan data. Statistically significant differences between the variables in comparison tests were not observed; for correlation tests, we found significant correlation only between FRT and the pressure center shifts in the anteroposterior direction of the dynamic tests. The study concluded that the achievement of TAF was not influenced by increased thoracic kyphosis angle.